2018
DOI: 10.1021/acs.inorgchem.8b01304
|View full text |Cite
|
Sign up to set email alerts
|

Visible Photosensitization of trans-Styrylpyridine Coordinated to fac-[Re(CO)3(dcbH2)]+: New Insights

Abstract: A strategic methodology has been developed to effectively synthesize the fac-[Re(CO) 3 (dcbH 2 )(trans-stpy)] + complex, where dcbH 2 = 2,2′-bipyridine-4,4′-dicarboxylic acid and trans-stpy = trans-4-styrylpyridine, which has been designed to efficiently absorb visible light. The complex exhibits outstanding trans-to-cis photoisomerization with 436 nm irradiation (Φ trans→cis = 0.50 ± 0.03), in contrast to the photochemical behavior previously reported in the literature (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 75 publications
(302 reference statements)
0
11
0
Order By: Relevance
“…The singlet MLCT excited state ( 1 MLCT) undergoes a fast intersystem crossing to the triplet excited state ( 3 MLCT) (27), which can transfer its energy to a triplet intraligand excited state ( 3 IL) localized on the photoswitchable fragment, finally producing a photoisomerization reaction (28). For example, fac-tricarbonyl Re(I) fragments have been used to promote the photoisomerization of stilbene-like and azobenzene ligands in the visible spectral region (29)(30)(31)(32)(33)(34). These compounds showed a remarkable cis ⇌ trans photoreversibility with quantum yield values as high as Φ trans?cis = 0.17-0.65 range and Φ cis?trans = 0.16-0.26 range, offering a new strategic approach to designing molecular switches (32,33).…”
Section: Introductionmentioning
confidence: 99%
“…The singlet MLCT excited state ( 1 MLCT) undergoes a fast intersystem crossing to the triplet excited state ( 3 MLCT) (27), which can transfer its energy to a triplet intraligand excited state ( 3 IL) localized on the photoswitchable fragment, finally producing a photoisomerization reaction (28). For example, fac-tricarbonyl Re(I) fragments have been used to promote the photoisomerization of stilbene-like and azobenzene ligands in the visible spectral region (29)(30)(31)(32)(33)(34). These compounds showed a remarkable cis ⇌ trans photoreversibility with quantum yield values as high as Φ trans?cis = 0.17-0.65 range and Φ cis?trans = 0.16-0.26 range, offering a new strategic approach to designing molecular switches (32,33).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the H 9 and H 10 protons experienced an upfield shift [Δδ­(H 9 ) = 0.60 ppm and Δδ­(H 10 ) = 0.61 ppm] accompanied by a decrease in the values of the coupling constant (from ∼16 to ∼12 Hz). The adjacent H 7 , H 8 , H 11 , and H 12 protons also underwent a measurable amount of upfield shift [Δδ­(H 7 ) = 0.12 ppm, Δδ­(H 8 ,H 11 ) = 0.09 ppm, and Δδ­(H 12 ) = 0.11 ppm] upon irradiation of up to 10 h. Such a change in the NMR spectra clearly goes in favor of the isomerization (t–t → t–c) behavior. ,, …”
Section: Resultsmentioning
confidence: 98%
“…Upon irradiation with 490 nm light, we found a gradual decrease in the intensity of peaks for the protons across the double bonds (H 9 and H 10 ) and the adjacent protons (H 7 , H 8 , H 11 , and H 12 ). Simultaneous evolution, together with gradual intensification of the peaks for the said protons, was found in the upfield region upon isomerization with time (H 7′ = 8.41 ppm, J = 7.5 Hz; H 8′ = 8.01 ppm, J = 7.5 Hz; H 9′ = 7.17 26,35,36 We tried to achieve the reverse isomerization process by keeping the isomerized form of the complexes, but it was found to be extremely slow. Further we tried irradiating the isomerized solution again by light of different wavelengths and found that irradiation with UV light of 280 nm can lead to the reverse isomerization process irrespective of solvents, although the process is very sluggish compared with the forward process.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Optically stimulated reversible trans-cis isomerization of stilbene appended heavier transition metal complexes (particularly Re, Ru, Ir and Pt) were thoroughly investigated by different research groups [46][47][48][49][50][51][52][53][54][55][56]. The results of these investigations laid the foundation for the construction of effective photo molecular switches.…”
Section: Introductionmentioning
confidence: 99%